Um estudo sobre o processo de singularização de crianças através do jogo protagonizado - Souza, Rubens André Carloto de (2010)
This study aims to understand the children’s singularization process in education from their interactions in situations of children’s role-playing games. The theoretical basis spans authors of the historical-cultural theory of the mind — especially Vygotsky, Leontiev and Elkonin —, some other theorists who deal with man’s psycho-social development and thinkers who discuss children’s games. According to theses references, we started from the premise of indispensability of social relationships and interactions in shaping personality, as well as the assumption that role-playing games is a fundamental activity for children’s psychological development, affecting their singularity. This empirical study was carried out on a federal childhood education school in Fortaleza. Thirteen children between 4 and 6 years of age were the research subjects. We used the method of participatory observation with ethnographic inspiration. The data were generated through shooting the children’s interactions in situations of role-playing game. Shootings were focused in role-playing action and negotiation episodes. The analysis was guided by microgenetic corpus interpretation, so that the study was carried out on the children’s discourse activities in interactive situations, in order to gather evidence of the singularization process in these episodes. The analytical concepts adopted consist of the main forms of interaction during role-playing games, which showed the children’s singularization process, namely: “protagonization”, “rule and role negotiation”, “role ando position swapping” and “drama”. The results show the way the children acted in negotiation moments; Their attitudes towards their peers, especially those of moving closer to or away from each other; the invitations to swap roles; power relationships; the way they performed their protagonizations; and the creative mechanisms used by children in developing their arguments and reconstructing social relationships are key elements of the singularization that emerge during the game.